Maternal RhD heterozygous genotype is associated with male biased secondary sex ratio - Kaňková, Šárka; Flegr, Jaroslav; Toman, Jan; Calda, Pavel (Early human development, 2020)
BACKGROUND: Previous studies suggest that RhD positive heterozygotes express better health status than RhD positive homozygotes and especially RhD negative subjects. This also applies to pregnant women. According to the Trivers-Willard hypothesis, women in better physical condition should have more sons. AIM: To test the hypothesis that RhD positive heterozygous mothers have a male-skewed sex ratio. STUDY DESIGN: Cross-sectional study. The data was analysed using Chi-Square test for all women, separately for RhD positive and RhD negative women, and separately for primiparous and multiparous women. The effects of maternal weight as a continuous predictor and the RhD phenotype of newborn as a categorical predictor of newborn sex were evaluated by the generalized linear model (GLZ) separately for RhD positive and RhD negative women using binomial distribution and logit link function. OUTCOME MEASURES: Clinical records comprised maternal weight before pregnancy, number of previous deliveries, sex of the newborn, maternal RhD phenotype, and RhD phenotype of the newborn. SUBJECTS: We analysed data from 5655 women who gave birth between 2008 and 2012 in General University Hospital in Prague. RESULTS: Secondary sex ratio was significantly higher (P = 0.028) in RhD positive mothers who had RhD negative newborns, i.e., in heterozygotes (SR = 1.23), than in RhD positive mothers who had RhD positive newborns, i.e., in a mixed population of heterozygotes and homozygotes (SR = 1.00), especially in primiparous women (P = 0.013; SR = 1.37 and 0.99 resp.). CONCLUSION: The sex ratio at birth was significantly higher in RhD positive mothers who had RhD negative newborns than in RhD positive mothers who had RhD positive newborns.
Keywords: Trivers-Willard hypothesis; Rh-Hr Blood-Group System; heterozygot; Male; Heterozygote; poměr pohlaví; Sex Determination Processes; zkreslení výsledků (epidemiologie); Adult; dospělí; RhD polymorphism; mužské pohlaví; porodnost; Sex Ratio; novorozenec; krevní skupiny - systém Rh-Hr; Sex ratio; lidé; Birth Rate; ženské pohlaví; Humans; Frequency-dependent selection; Bias; Infant, Newborn; Heterozygote advantage; procesy určující pohlaví; Female